An investigation into the biomechanical effects of tibial vertical cutting errors on the proximal tibia after unicompartmental knee arthroplasty and the improvement of cutting planes - Deyan Ou; Gaoyong Deng; Gaosheng Qin; Yongqing Ye; Jingwei Pan; Yu Huang; Haisheng Kuang; Shilin Tang; Yongxin Mo; Shixin Pan (BMC Musculoskeletal Disorders)
Abstract Objective Unicompartmental knee arthroplasty (UKA) has shown significant clinical effectiveness in treating medial compartment knee degeneration, but postoperative periprosthetic fractures and persistent pain remain common and challenging complications. Tibial vertical cutting errors are considered an important factor influencing postoperative biomechanics. This study aims to investigate the biomechanical effects of tibial vertical cutting errors(referring to the deviation between the actual vertical cutting plane and the ideal vertical resection plane during UKA)on the proximal tibia after UKA and to reduce the risk of fractures and improve postoperative outcomes through surface modification designs (chamfering and filleting). Methods In this study, a three-dimensional model of the tibia was constructed from CT and MRI data of a 26-year-old male volunteer. Finite element analysis (FEA) was used to simulate different vertical cutting errors (1 mm, 3 mm, 5 mm, 7 mm, and 9 mm). The study included models with varying cutting errors and two surface modification designs. During the simulation, stress and strain distribution on the proximal tibia were analyzed to assess the impact of cutting errors on the risk of periprosthetic fractures. Additionally, the fracture risk was quantified using the Risk of Fracture(ROF) index, and statistical data analysis and comparison were performed. Results The results showed that as the vertical cutting error increased, the equivalent stress and fracture risk value beneath the tibial prosthesis significantly increased. Notably, in the 5–9 mm cutting error models, the fracture risk was markedly higher. The chamfering and rounding designs effectively reduced stress concentration beneath the tibial prosthesis, lowering the stress peaks and significantly decreasing the fracture risk. In the ROF calculation, when the vertical cutting error exceeded 5 mm, the ROF value significantly exceeded the critical value, indicating a substantial increase in fracture risk. Compared to the standard osteotomy method, both surface modification designs effectively reduced the fracture risk. Conclusion Tibial vertical cutting error is a significant risk factor for periprosthetic fractures and pain after UKA. The greater the vertical cutting error, the faster the fracture risk and bone degeneration progress. Specifically, when the vertical cutting error exceeds 5 mm, the fracture risk increases significantly. The surface modification design proposed in this study effectively mitigates the negative biomechanical effects of cutting errors on the tibia and reduces the risk of postoperative complications. Future research should further explore the impact of other factors, such as osteoporosis, activity level, and muscle strength, on UKA outcomes, and incorporate advanced surgical navigation technologies to improve surgical precision and reduce errors.